Membangun Kepercayaan Diri Siswa dalam Berbicara Melalui Kegiatan Bercerita (Storytelling) - Fitriyani Bakri; Muhammad Hasbi; Abdul Halim; Auliyanti Sahril Nurfadilah; Nur Mutmainnah Halim (Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Speaking skill is one of the main components in English language learning that requires students’ courage and self-confidence. However, many senior high school students still face psychological barriers in expressing themselves orally. This community service program aimed to enhance students’ confidence in speaking through storytelling activities within the context of English language learning. The program was conducted at SMAN 8 Makassar and involved 23 students who were guided and mentored by a team from the Department of English, Faculty of Languages and Literature, Universitas Negeri Makassar, along with students participating in the Asistensi Mengajar Mandiri (AjarMi) program. The implementation method consisted of three stages: preparation, the storytelling workshop, and evaluation through observation and student reflection. The results of the program indicated a significant improvement in students’ self-confidence, speaking fluency, and expressive ability. This activity also demonstrated effective collaboration among the university, student teachers, and the school in promoting communicative and humanistic language learning.